2004
DOI: 10.1021/jm040082s
|View full text |Cite
|
Sign up to set email alerts
|

β-Oxygenated Analogues of the 5-HT2ASerotonin Receptor Agonist 1-(4-Bromo-2,5-dimethoxyphenyl)-2-aminopropane

Abstract: Activation of 5-HT(2A) serotonin receptors represents a novel approach to lowering intraocular pressure. Because 5-HT(2A) serotonin receptor agonists might also produce undesirable central effects should sufficient quantities enter the brain, attempts were made to identify 5-HT(2) serotonin receptor agonists with reduced propensity to penetrate the blood-brain barrier. 1-(4-Bromo-2,5-dimethoxyphenyl)-2-aminopropan-1-ol (6), an analogue of the 5-HT(2) serotonin receptor agonist 1-(4-bromo-2,5-dimethoxyphenyl)-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 22 publications
0
26
0
Order By: Relevance
“…Glennon et al 52 have studied the effect of β-oxygenation on the 5-HT 2A agonist properties of 1-(2,5-dimethoxy-4-bromophenyl)-2-aminopropane (DOB) (Figure 16). The four stereoisomers of the β-oxygenated compounds were studied, either with a β-OH or a β-OCH 3 .…”
Section: β-Oxygenationmentioning
confidence: 99%
“…Glennon et al 52 have studied the effect of β-oxygenation on the 5-HT 2A agonist properties of 1-(2,5-dimethoxy-4-bromophenyl)-2-aminopropane (DOB) (Figure 16). The four stereoisomers of the β-oxygenated compounds were studied, either with a β-OH or a β-OCH 3 .…”
Section: β-Oxygenationmentioning
confidence: 99%
“…[9] The synthesis of bk-2C-B was first published in 2004 where it served as an intermediate for the preparation of 2-(4-bromo-2,5-dimethoxyphenyl)morpholine. [10] The synthesis and extensive analytical characterization of bk-2C-B, verifying the identification of this substance obtained from a test purchase from an Internet vendor, was reported more recently. Furthermore, it was reported that bk-2C-B was prone degradation when analyzed by GC-MS without derivatization.…”
Section: Introductionmentioning
confidence: 65%
“…The retention times increased as a reflection of increased mass of the iodine substituent. Products analogous to bk-2C-B (1-4), (6)(7)(8) and (10) were also formed during the pyrolysis of bk-2C-I. Two additional pyrolysis products were detected and tentatively identified through interpretation of their EI mass spectra.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…[49] 1 H NMR spectra have been reported for 25B-NBOMe in DMSO-d6 [16,37] and in CDCl3 [15,50] ; for 25C-NBOMe in DMSO-d6, [37] in CDCl3, [51] and in CD3OD [16,52] ; for 25I-NBOMe in DMSO-d6, [16,37,53] in CDCl3, [15,[54][55][56] and in CD3OD [57] ; for 25I-NBOH in DMSO-d6 [15,16,37] ; for 25I-NBMD in DMSO-d6. [16,37] The 4-R family: 4-alkyl-2,5-dimethoxyphenyl pattern…”
mentioning
confidence: 99%